Do Funding Resources Affect the Accountability Disclosure of Non-Profit Organizations? - Nik Azman, Nik Amalena Najebah; Arshad, Roshayani; Abu Bakar, Noorbijan (Asian Journal of Accounting Perspectives, 2015)
Accountability is important in Non-profit Organizations (NPOs) since their key revenue resources are donations and contributions from the public and various parties. This implies that NPOs are accountable to various stakeholders. In Malaysia, the growing number of NPOs shows how important NPOs are in contributing to society in terms of social work. By championing the need of the people through their activities, NPOs enjoy public trust since their goal is to help the people, and not for profit motivation. However, many NPOs are generally reluctant to share more comprehensive information and may not recognize the need for accountability by the NPOs. These problems could be solved if the enforcement and monitoring mechanisms are efficiently practiced. Using content analysis of annual reports and the Financial Information Forms/Borang Maklumat Kewangan (BMK) of 219 societies registered with the Companies Commission of Malaysia (CCM), this study examines the relationship between organizational characteristics and accountability in NPOs. The characteristics of organizational characteristics examined are grants and donations. The resource dependency theory is used to explain the organizational characteristics. The results of this study provide evidence that organizational characteristics are not significantly related to the accountability of NPOs. In relation to the insignificant results for organizational characteristics, it may indicate that non-profit managers are not using their disclosure effectively to manage inter-organizational relationships to ensure the continuous flow of financial and other resources to their organizations. Overall, the findings provide useful information that gives more input to the various regulatory authorities and other relevant stakeholders concerning the accountability disclosure of NPOs in Malaysia.